PROBLEMS OF CHILDHOOD AND EDUCATION IN CH.DICKENS’ WORK.S - Nafisa Raimovna Kobilova; Mavlonova Maftuna Baxodir qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In Charles Dickens' works, the themes of childhood and education are prominent, reflecting the social challenges faced by children in Victorian England. Through characters like Oliver Twist and Pip, Dickens exposes the harsh realities of child labor, lack of access to education, child abuse, and social inequality. His narratives vividly depict the struggles and resilience of disadvantaged children, calling attention to the need for reform and compassion in addressing these issues. Dickens' enduring exploration of childhood adversity and societal injustice continues to resonate with readers, highlighting the enduring relevance of his social critiques.